WOMEN'S HEALTH INCARCERATED: A PROPOSAL FOR INTERVENTION, LOVE AND LIFE - Marlene Menezes de Souza Teixeira; Sebastiana Micaela Amorim Lemos; Elizangela Beneval Bento; Diogo Onofre Gomes de Souza; Maria Rosa Chitolina Schetinger (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
Identify and understand the situation of incarcerated women and access to health in the prison system. The study was conducted by a health professional (nurse) and with the participation of twenty students of the nursing course of a private university. The data were collected in interviews and the written responses and grouped into categories through content analysis, we studied 38 women prisoners in the age group of 18 to 40 years. We identified socioeconomic data, as well as the discourses of women prisoners who revealed the point of view on health care, prevention and promotion received in prison, knowledge about the sexual diseases that affect them, as well as treatment and education in health, opinions on the campaigns and advertisements of the Ministry of Health aimed at women and interests on subjects to be discussed in the next meetings. Este estudo revela à importância de políticas públicas que estabeleçam estratégias de prevenção e promoção a saúde na busca por uma qualidade de vida destas mulheres. This study reveals the importance of public policies that establish prevention strategies and promote health in the quest for a quality of life of these women.